2002
DOI: 10.1002/pola.10276
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and in vitro degradation of liquid‐crystalline terpolyesters of 4‐hydroxyphenylacetic acid/3‐(4‐hydroxyphenyl)propionic acid with terephthalic acid and 2,6‐naphthalene diol

Abstract: Melt-processable liquid-crystalline terpolyesters of 4-hydroxyphenylacetic acid (HPAA) and 3-(4-hydroxyphenyl)propionic acid (HPPA) with terephthalic acid and 2,6-naphthalene diol were synthesized by one-step acidolysis melt polycondensation followed by postpolymerization and were characterized with viscosity studies, Fourier transform infrared (FTIR) and NMR spectroscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), polarized light microscopy, and wide-angle X-ray diffraction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In the case of polyesters based on phloretic acid, little work has been reported on its homopolymer, and most studies have been conducted on its binary copolymers with other aromatic comonomers . The formation of terpolymers of phloretic acid also has been reported . The homopolymer of phloretic acid and its copolyesters with p ‐hydroxybenzoic acid were shown to be liquid crystalline.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of polyesters based on phloretic acid, little work has been reported on its homopolymer, and most studies have been conducted on its binary copolymers with other aromatic comonomers . The formation of terpolymers of phloretic acid also has been reported . The homopolymer of phloretic acid and its copolyesters with p ‐hydroxybenzoic acid were shown to be liquid crystalline.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradability of synthetic polymers has been a great concern for all synthetic polymer chemists and our early attempts at making LC polymers biodegradable were described earlier [193][194][195][196]. We then tried to synthesize biodegradable poly(esteramides) by controlling the crystallinity and aliphatic ester content [221][222][223].…”
Section: 'Synthetically-inspired' Materials From Natural Monomersmentioning
confidence: 99%
“…7. A new monomer 8-hydrooxyphenyl octanoic acid was prepared by phase-transfer-catalyzed permanganate oxidation of cardanol a series homo-polymers and LCPs were prepared and characterized including LCP blends [192][193][194][195][196][197][198][199][200][201][202]. The polymers were shown to hydrolytically degradable.…”
Section: 'Synthetically-inspired' Materials From Natural Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough understanding of structure−property relationships with respect to biodegradability is of fundamental importance for the tailored design of polymeric materials for tissue engineering. Most recently, hydrolytic and enzymatic degradation of aromatic / aliphatic copolyesters in vitro have been reported by several groups. , Nagata et al has presented degradation of thermotropic copolyesters based on terephthalic acid, 3-(4-hydroxyphenyl)propionic acid, and glycol by enzyme. Prasad et al reported in vitro degradation of liquid-crystalline terpolyesters of 4-hydroxyphenylaliphatic acid with terephthalic acid and 2,6-naphthalene diol.…”
mentioning
confidence: 99%